2020
DOI: 10.32509/wacana.v19i1.1008
|View full text |Cite
|
Sign up to set email alerts
|

Dominasi Perempuan Pebisnis Dalam Rumah Tangga

Abstract: Women as business people are no longer taboo and foreign for at least the past decade. The data shows an increase in the number of women as business people continues to increase from year to year no exception in the city of Pekanbaru. This research aims to find out how women's business domination in the household in Pekanbaru. The study used qualitative techniques with a phenomenological study approach and a constructivism paradigm.  Some of  the things that became the focus of the analysis in this study: how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, Chaula Luthfia found multiple and unequal roles for a wife, namely being a housewife and earning a living (Luthfia, 2021). Ikhma Zurani, in his research, found that businessmen's wives have the power to decide business and family financial affairs (Zurani, 2020). Siti Khoirotul Ula discusses leadership in the family with the theory of mubilah.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Chaula Luthfia found multiple and unequal roles for a wife, namely being a housewife and earning a living (Luthfia, 2021). Ikhma Zurani, in his research, found that businessmen's wives have the power to decide business and family financial affairs (Zurani, 2020). Siti Khoirotul Ula discusses leadership in the family with the theory of mubilah.…”
Section: Introductionmentioning
confidence: 99%
“…Konsep kewirausahaan pertama kali dicetuskan pada tahun 1700-an, dan mengacu pada kegiatan yang berkaitan dengan upaya untuk mendirikan industri atau pendirian usaha. Kewirausahaan memiliki arti yang berbeda bagi orang yang berbeda (Zurani, 2020). Dalam praktiknya, Kewirausahaan adalah tentang menciptakan sesuatu yang baru atau menemukan cara baru untuk membuat sesuatu yang sudah ada.…”
unclassified